Eggs of a Eusial Aphid’s Predator are Protected Against Attacks by Aphid Soldiers - Hattori, Mitsuru; Itino, Takao (Sociobiology, 2014)
Predators generally have traits that enable them to efficiently capture their prey and thus improve their survival. Natural selection should also favor traits of predators that improve the survival rate of their eggs, which are immobile and incapable of active resistance. We hypothesized that eggs of Atkinsonia ignipicta, a specialist predator of the eusocial aphid Ceratovacuna japonica, exhibit a defensive trait against aphid soldiers. We found that the hatchability of A. ignipicta eggs did not differ significantly between the experimental treatments with and without soldiers, which suggests that the eggs have a defensive trait that protects them from soldier aphids. Moreover, although the soldiers occasionally exhibited attack behavior when they encountered an egg, they did not continue the attack. We have observed a similar interruption of attack behavior by soldiers that attacked their aphid siblings by mistake, suggesting that the eggs may chemically mimic the soldiers' siblings. This study thus provides evidence for adaptation in a specialist predator of a eusocial aphid.